(untitled) (Годишник на УНСС, 2021)
In recent years, Bulgarian society has witnessed a number of abuses by the management of professional football clubs. However, these vicious practices are not a precedent. Although this activity is controlled by: the football federations of the respective country, the Federation Internationale de Football Association (FIFA) and the Union of European Football Associations (UEFA), this is not enough. It is important to take measures to counter crime, like: money laundering, corruption, fixing matches, illegal performance enhancing technology, sporting related financial irregularities, management related financial irregularities, transfer of young players across borders. In this line, the United Kingdom is developing a special mode to prevention from crimes in the football games.